ASI eksklusif berhubungan dengan perkembangan bayi di Kecamatan Gading Cempaka Kota Bengkulu - Kamsiah .; Detty Siti Nurdiati; Emy Huriyati (Alma Ata University Press, 2013)
ABSTRACTBackground: Malnutrition is a major problem in Indonesia nowadays. Malnutrition will affect the quality of human resources in the future. Age of 7–12 months is a critical and golden period for the process of child development. Early complementary breastfeeding is one of causes the prevalence child development disorder.Objective: To ﬁ nd out the relationship between exclusive breastfeeding and the development of infants 7–12 months old at the Health Center at Jalan Gedang, Sub District of Gading Cempaka, Bengkulu Municipality.Method: This observational study used cross sectional design. There were as many as 75 samples of infants 7–12 months old taken using cluster random sampling. Data of breastfeeding were obtained from questionnaires, data of development were obtained from questionnaires with pre-screening development format. Data analysis used chi square and logistic regression statistical test.Result: There was signiﬁ cant relationship between exclusive breastfeeding and infant development (p<0.05). There was signiﬁ cant relationship between birth weight and infant development (p<0.05). There was no signiﬁ cant relationship between method of childbirth, education of mothers, mothers’ occupation, family income and infant development (p>0.05). The result of multivariable analysis showed that birth weight was a predictor of infant development (OR= 5.231).Conclusion: There was signiﬁ cant relationship between exclusive breastfeeding and the development of infants of 7–12 months old. Birth weight was a dominant factor related to the development of infants of 7–12 months old.KEYWORDS:exclusive breastfeeding, infant developmentABSTRAKLatar belakang: Malnutrisi menjadi masalah utama di Indonesia yang akan berpengaruh terhadap kualitas sumber daya manusia pada masa yang akan dating. Usia 7-12 tahun merupakan masa kritis dan masa keemasan bagi perkembangan anak. Pemberian MPASI (makanan pendamping ASI) yang terlalu dini merupakan salah satu penyebab gangguan perkembangan bayi.Tujuan: Untuk mengetahui hubungan antara ASI eksklusif dengan perkembangan bayi di Puskesmas Jalan Gedang Kecamatan Gading Cempaka Kota Bengkulu.Metode: Jenis penelitian ini adalah observasional menggunakan rancangan cross sectional. Jumlah sampel adalah 75 bayi berusia 7-12 bulan yang dipilih menggunakan simple random sampling.Data diperoleh melalui kuesioner dan wawancara, kemudian dianalisis menggunakan uji Chi Square dan regresi logistik dengan conﬁ dence interval (CI) 95%.Hasil: Ada hubungan bermakna antara ASI eksklusif dengan perkembangan bayi dan antara berat badan lahir dan perkembangan bayi (p<0.05), namun tidak ditemukan hubungan antara metode persalingan, pendidikan ibu, pekerjaan ibu, dan pendapatan keluarga dengan perkembangan bayi (p>0,05). Hasil analisis multivariat menunjukkan bahwa berat badan lahir merupakan prediktor perkembangan bayi (OR=5,231).Kesimpulan: Ada hubungan bermakna antara ASI eksklusif dengan perkembangan bayi 7-12 bulan. Berat badan lahir merupakan faktor dominan yang berhubungan dengan perkembangan bayi 7-12 bulan.KATA KUNCI: ASI eksklusif, perkembangan bayi